Clinical Remission as Defined by the Mayo Score: Do We Deceive Ourselves?. Issue 1 (January 2015) - Samaan, Mark A.; Feagan, Brian G.; Sandborn, Willam J.; Levesque, Barrett G.
Abstract : Article first published online 4 December 2014